Kesan kaedah flipped classroom menerusi pembelajaran berasaskan projek ke atas pencapaian dan gaya pembelajaran pelajar - A. Rahman, Azlina (2017)
Flipped classroom is a 21st century learning approach, which prepares students for understanding the concept of a topic before learning in the classroom. Flipped classroom is proposed as a solution to facilitate learning of Mathematics among students. The research studied the effects of the flipped classroom approach through project based learning to maximize students‟ achievements in a difficult subject, such as Mathematics. This study was preceded by determining the dominant learning style using the Learning Style Questionnaire. The Learning Style Questionnaire consists of individual and group constructs. A quasi experimental design was conducted to measure the students‟ achievement through the analysis of ANCOVA. 61 Form Two students from a boarding school were selected, and 31 students were selected for the treatment group while 30 students were selected for the control group. The treatment group experienced the flipped classroom approach while the control group was conducted in a conventional class. Students‟ perceptions were obtained through the Students‟ Engagement Questionnaire while the students‟ experiences were obtained through the Flipped Classroom Questionnaire and interview sessions. A pilot study was conducted to obtain the validity and reliability of all the instruments. The findings suggest that the most dominant learning style of the students before the execution of the flipped classroom method was the group learning style. Meanwhile, the finding from the Achievement Test showed that the treatment group had experienced a significant improvement in grades compared to the control group. Moreover, from the project based learning, a rubric analytical instrument showed the potentials to form individual or group learning style. The findings from the Learning Style Questionnaire after the treatment showed that a number of students had succeeded to master the two types of learning comprising individual and group learning. Finally, a framework for students‟ engagement in learning based on learning styles to improve students‟ achievement through project based learning in flipped classroom was developed through a tree analysis using the concept of probability. The framework of this flipped classroom research can be used by students and serves as a guide for teachers to execute the approach through project based learning effectively and systematically.